Digestive endoscopy during the COVID-19 pandemic - Nélcido Luis Sánchez García; Mirta Infante Velásquez (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: COVID-19 is the disease caused by the infection of the new SARS-CoV-2 coronavirus which was discovered at the end of 2019 in China and has caused millions of patients worldwide. Objective: To describe the work characteristics related to digestive endoscopy during the COVID-19 pandemic. Material and methods: A bibliographic review was carried out using bibliographic databases, guides and search engines. Information from national and international sites was used. The quality and validity of the selected articles were analyzed. Development: The transmission of SARS-CoV-2 has been determined by several routes, the respiratory one being the most accepted in which there is a generation of aerosols that are also produced through endoscopic procedures. For this reason, different guidelines and care protocols have been established to perform safe endoscopies for patients and endoscopy personnel. Conclusions: In the face of the COVID-19 pandemic, prevention is the most important strategy, putting the world's health systems to the test and implementing adjusted forms of medical care to prevent the spread of the disease in patients and healthcare personnel.